ANALISIS KUALITAS AIR SUNGAI SEPAKU SEBAGAI PENYEDIA AIR BERSIH DI IBU KOTA NUSANTARA (IKN), KALIMANTAN TIMUR - Azwari, Fachruddin; Siahaya, Martha E.; Hadidjah, Kemala; Supriadi, Adi; Benedicta, Christine Elia (Jurnal Nusa Sylva, 2025)
Sepaku River is one of the primary water resources planned to meet the raw water needs of Nusantara Capital City (IKN) in East Kalimantan, Indonesia. This study aims to analyze the water quality of the Sepaku River based on physical, chemical, and microbiological parameters, and to evaluate the differences in water quality at three locations: upstream, midstream, and downstream. The parameters analyzed include pH, Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Coliform. Data were collected through field surveys and laboratory tests, and analyzed using One-Way ANOVA and Spearman's Rank Correlation. The results show that while the pH levels still meet the water quality standards, TSS, BOD, and Total Coliform exceed the established thresholds. The ANOVA test indicates a significant difference in TSS among the sampling locations, while other parameters show widespread contamination. The Spearman Correlation reveals significant relationships between TSS and BOD, and between BOD and Total Coliform. These findings indicate that pollution in the Sepaku River is complex and interrelated across different parameters. Therefore, integrated and ecosystem-based water quality management is required to support the provision of safe and sustainable raw water for Nusantara Capital City.